2019
DOI: 10.1186/s13034-019-0299-7
|View full text |Cite
|
Sign up to set email alerts
|

Executive functioning and neurodevelopmental disorders in early childhood: a prospective population-based study

Abstract: BackgroundExecutive functioning deficits are common in children with neurodevelopmental disorders. However, prior research mainly focused on clinical populations employing cross-sectional designs, impeding conclusions on temporal neurodevelopmental pathways. Here, we examined the prospective association of executive functioning with subsequent autism spectrum disorder (ASD) traits and attention-deficit/hyperactivity disorder (ADHD) traits.MethodsThis study included young children from the Generation R Study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 78 publications
0
18
0
1
Order By: Relevance
“…11 Deficits in EF could bring to school underachievement, emotional-behavioral problems, neurodevelopmental disorders, and poor physical health, including obesity. 12,13 However, the results from several studies of the relationship between obesity and EF were mixed and inconclusive. [14][15][16][17][18][19][20] Despite extensive systematic reviews and meta-analyses conducted in a wide range of ages, the direction of the relationship has not been conclusive.…”
mentioning
confidence: 99%
“…11 Deficits in EF could bring to school underachievement, emotional-behavioral problems, neurodevelopmental disorders, and poor physical health, including obesity. 12,13 However, the results from several studies of the relationship between obesity and EF were mixed and inconclusive. [14][15][16][17][18][19][20] Despite extensive systematic reviews and meta-analyses conducted in a wide range of ages, the direction of the relationship has not been conclusive.…”
mentioning
confidence: 99%
“…Furthermore, previous research has found evidence that executive function may be impaired in individuals with neurodevelopmental disorders (Otterman et al, 2019), including autism spectrum disorder (ASD; Christ et al, 2011;Adams and Jarrold, 2012;Murphy et al, 2014), attention-deficit hyperactivity disorder (ADHD; Arnsten and Li, 2005;Wilens and Spencer, 2010), and developmental coordination disorder (DCD; Bernardi et al, 2017). Since difficulties with executive functioning predict poorer academic achievement (Zelazo and Carlson, 2020), and executive function impairments seem to occur in neurodevelopmental disorders such as autism, ADHD, and DCD (Holst and Thorell, 2019;Omer and Leonard, 2021), individuals with these conditions may be particularly at risk of academic underachievement.…”
Section: Executive Function and Academic Achievementmentioning
confidence: 99%
“…Several studies have identified that school-aged children with ADHD show poorer performance in working memory and processing speed than in perceptual and verbal functional domains when compared with their peers of average intelligence [ 27 , 28 , 29 , 30 , 31 , 32 ]. Regarding preschool children, the deficits in varied executive functioning, including inhibition control, working memory, speed of processing, and planning/organization, may be general markers of ADHD [ 33 , 34 , 35 , 36 , 37 , 38 ]. However, ADHD appears to be characterized by neurobehavioral heterogeneity both in preschool and school-age children; the subgroup of youths with ADHD may perform at a high level (as high as their neurotypical counterparts) on related tasks [ 32 , 34 , 39 ].…”
Section: Introductionmentioning
confidence: 99%